2001
DOI: 10.1007/s11908-001-0062-z
|View full text |Cite
|
Sign up to set email alerts
|

Tapeworms

Abstract: Tapeworms are among the oldest afflictions of humans. They continue, even today, to be an important cause of morbidity and mortality, worldwide. Taenia saginata and Taenia solium infections are still common in many developing countries. Diphyllobothrium latum infections, are decreasing, but this tapeworm, transmitted to humans through the eating of raw salmon, can cause severe anemia. Hymenolepis and Dipylidium infections may occur to children. Hydatid disease is a common cause of morbidity, especially among i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…In the developing world intestinal parasitic infection is still an important cause of morbidity and mortality. [8] The present study results showed the occurrence of several intestinal parasites of public health importance in people residing in this area. The prevalence was found to be 11.62% which is in agreement with the studies from Puducherry by Ragunathan to 66% with varying prevalence for individual parasites.…”
Section: Discussionsupporting
confidence: 57%
“…In the developing world intestinal parasitic infection is still an important cause of morbidity and mortality. [8] The present study results showed the occurrence of several intestinal parasites of public health importance in people residing in this area. The prevalence was found to be 11.62% which is in agreement with the studies from Puducherry by Ragunathan to 66% with varying prevalence for individual parasites.…”
Section: Discussionsupporting
confidence: 57%
“…On a worldwide scale, new infections of humans are reported regularly, particularly from Russia and parts of Japan, whereas infections seem to be declining in North America and Europe; however, it is unclear if sources of the infection are also decreasing or if public health awareness has improved in industrialized countries. In South America and elsewhere, an increase in reports from fish, especially salmonids, suggest relatively high levels in Salmonidae (Dick et al 2001;Tanowitz et al 2001). Globally, new species have been described and the etiology of the disease may be changing.…”
Section: Sources and Prevalence Of Tapeworm Infectionsmentioning
confidence: 99%
“…A number of recent publications suggest that administration of albendazole for 28 days followed by ultrasonic or CTguided percutaneous drainage of hydatid cysts, followed by injection of a scolicidal agent, is a reasonably safe and effective alternative to surgery in persons with uncomplicated disease [1,[6][7][8]. Albendazole is continued after the procedure.…”
Section: Editor's Commentsmentioning
confidence: 99%
“…cause of disease in the Middle East and other endemic areas, and it is occasionally encountered in industrialized countries among immigrants or long-term travelers [1]. Patients with echinococcosis frequently pose substantial therapeutic challenges.…”
mentioning
confidence: 99%